Association of second-hand smoke exposure at home with psychological distress in the Spanish adult population. (November 2015) - Ballbè, Montse; Martínez-Sánchez, Jose M.; Gual, Antoni; Martínez, Cristina; Fu, Marcela; Sureda, Xisca; Padrón-Monedero, Alicia; Galán, Iñaki; Fernández, Esteve
Abstract: Introduction: Second-hand smoke (SHS) exposure has been associated with increased risks of respiratory and heart diseases. However, little is known about the potential effects of SHS on psychological distress. The aim of this study is to examine the association of SHS exposure at home with psychological distress in Spain. Methods: A cross-sectional survey about SHS exposure, socio-demographic and health related variables, and psychological distress, measured with the 12-item version of the General Health Questionnaire (GHQ-12) with a cut-off score ≥ 3, was conducted from 2011–2012 among a representative sample of the adult population (aged ≥ 15 years) of Spain. From the total sample (n = 21, 007), we used the subsample of never-smokers (n = 11, 214). We computed the odds ratios (OR) and their 95% confidence intervals (95% CI) for scoring ≥ 3 on the GHQ by means of unconditional multiple logistic regression models adjusted for sex and age. Results: In the subsample, 9.7% (n = 1, 090) responded that they were exposed to SHS at home. The prevalence of subjects scoring ≥ 3 on the GHQ was higher for the sample exposed to SHS (22.7%) than for the non-exposed sample (18.9%; OR: 1.39; CI: 1.19–1.62). This association was also present when stratified for sex, age, marital status, socio-economic status, perceived general health, presence of any chronic disease, and alcohol intake. Conclusions: Exposure to SHS at home is associated with psychological distress. Further investigation is necessary to determine if this association is causal. Avoiding SHS exposure at home could have beneficial effects on psychological distress. Highlights: The potential effects of SHS on psychological distress have been scarcely addressed. The study is conducted on a representative sample of the adult population of Spain. Prevalence of psychological distress is higher in those exposed to SHS at home. Avoiding SHS exposure at home may have beneficial effects on psychological distress.